세가지 다른 모형의 덕트 프로펠러의 CFD 해석과 시험에 관한 연구 - 정태환(Tae-Hwan Joung); 정성재(Seong-Jae Jeong); 이승건(Seung-Keon Lee) (Han-guk haeyang gonghak hoeji (Online), 2014)
In this study, propeller open water characteristics ($K_P$, $K_T$ and ${η}_o$) were compared for three different ducted propellers using a Computational Fluid Dynamics (CFD) analysis, as well as an experimental test at a basin. The best shape of the duct was selected from the three types of specially designed ducts based on the CFD analysis results. The same propeller model (Kaplan type propeller) was used inside all three duct models, and the propeller open water characteristics were compared, predominantly at the design speed for an underwater vehicle. Finally, the results of the CFD test simulations for the selected duct case were verified by experimental open water tests in a towing tank.